Resveratrol loaded glycyrrhizic acid-conjugated human serum albumin nanoparticles for tail vein injection II: pharmacokinetics, tissue distribution and bioavailability. (1st January 2020) - Wu, Mingfang; Zhong, Chen; Deng, Yiping; Zhang, Qian; Zhang, Xiaoxue; Zhao, Xiuhua
Abstract: There are many kinds of biological activities of resveratrol itself, but its clinical application is limited by its poor solubility in water and low bioavailability. Therefore, we have prepared glycyrrhizic acid-conjugated human serum albumin nanoparticles wrapping resveratrol nanoparticles (GL-HSA-RESNPs). The purpose of this study was to investigate the bioavailability, pharmacokinetics and tissue distribution of resveratrol in rats after single-dose tail vein injection administration of GL-HSA-RESNPs. A sensitive and reliable high performance liquid chromatography (HPLC) method was established to verify the content of resveratrol in rat plasma and organs. The C max value after GL-HSA-RESNPs administration was significantly higher than that of resveratrol suspension (933 ± 76.64 ng/mL vs . 618 ± 42.54 ng/mL, p < .01). The T max value obtained after GL-HSA-RESNPs administration was significantly shorter than that after resveratrol suspension administration (0.17 ± 0.01 h vs . 0.25 ± 0.01 h, p < .001). The bioavailability of GL-HSA-RESNPs was 4.25 times higher than that of the pure resveratrol. The concentration of resveratrol in the main organs of rats treated with the GL-HSA-RESNPs was higher than that in rats treated with the pure resveratrol. Rats treated with GL-HSA-RESNPs had the highest concentration of resveratrol in their liver. It is indicated that GL-HSA-RESNPs is a promising liver-targeted delivery system that improves the in vivo bioavailability of resveratrol.